Newspapers and politics in Malaysia: the coverage of Islam-related news during the 13th General Election - Sedu, Nerawi; A.Manaf, Aini Maznina (2013)
Mass media play a very signigicant role in politics. Mass media coverage of certain issues during political campign either increases or decreases the chance of gaining votes for any political parties and political leaders. This study was aimed at examining the Islam-related issues covered by the mainstream newspapers in Malaysia during the General Election 13. In this study, the data were collected from four Malaysian mainstream newspapers, comprising of two Malay and two English newspapers. The selected newspapers were Berita Harian, Utusan Malaysia, The Star and New Straits Times. The data were collected starting from 20 of April 2013 until 6 of May 2013. Rationally, the news that came out in the newspapers beginning the nomination day until the voting day might affect or influence voters’ decisions. A total of 178 news articles were analysed using content analysis. It was found that there were 15 issues frequently reported in the newspapers during that period. Among the most frequently reported Islam-related issues were Hudud, Islamic state, kalimah Allah (the word ‘Allah’), Qazaf (slanderous accusation)/sumpah laknat (a retributive oath under syari’ah laws), and apostasy/Aqidah. It was also found that most of these issues were covered the Malay newspapers. In addition, the data also indicated that most of the news were inclined towards supporting the ruling party i.e. Barisan Nasional. The frequent coverage of these issues were seen as one of the strategies used by the political parties to gain votes in the GE13.